Implementation of Slum Settlement Management Policies in the District of Lima Puluh Kota Pekanbaru - Trio Saputra; Alexsander Yandra; Meiliani Zahra; Eka Eka; Wasiah Sufi (Jurnal Manajemen Pelayanan Publik, 2022)
This study aimed to determine and explain the implementation of policies for handling slum settlements in Lima Puluh Kota Pekanbaru. This research uses a qualitative method with a descriptive approach that aims to describe the relationship between the phenomena investigated. Qualitative data analysis is carried out interactively and takes place continuously until complete so that the data is saturated. The study results indicate that the government's resources are limited in implementing the handling of slum settlements. For this reason, there is a need for collaboration between the government and the private sector. The role of the private sector also includes the contribution of funds through private investments that are beneficial to support the process of handling slum settlements. The monitoring and evaluation of the private sector also contribute to maintaining the results obtained through community empowerment projects from some of the profits from private investments that have been operating and increasing the amount of the budget by field needs.